Juridical Study on Minors Riding Motorcycles for Junior High School Students - Dimas Galih Saputra (UM Purwokerto Press, 2023)
This research aims to find out the factors behind minors or junior high school students riding motorbikes and to find out the legal arrangements for minors riding motorbikes. The research method used is the Normative research method. The method of collecting legal materials used is document study and literature study. The results of this study indicate that the factors that cause children to ride motorbikes to school are internal factors; (1) self-will (2) freedom (3) time and mileage efficiency (4) prestige (5) mass media. External factors; (1) family factors (2) school environment (3) peers (4) lack of public transportation. Then another result is to know the study of the regulations of minors riding motorbikes referring to Law Number 22 of 2009 concerning Road Traffic and Transportation. Therefore, the conclusion of this article is that there are many factors that cause junior high school children and also know the existence of regulatory restrictions on minors riding motorbikes referring to Law Number 22 of 2009 concerning Road Traffic and Transportation.